Systematic Literature Review: Peranan Fly ash, Silika, dan Slag Sebagai Bahan Tambahan dalam Meningkatkan Kekuatan Tekan Dini Beton - Bara, Alvin Alfredo (Jurnal Kridatama Sains dan Teknologi, 2025)
This study aims to systematically evaluate the role of mineral admixtures—Fly ash, silica (silica fume and nano-silica), and Slag (GGBFS)—in enhancing the early compressive strength of concrete within 1 to 7 days of curing. To achieve this objective, a Systematic Literature Review (SLR) was conducted by analyzing seven selected international research articles published between 2023 and 2025. The review focused on admixture types, mix proportions, particle sizes, types of activators, curing methods, and early-age compressive strength results. The findings reveal that while Fly ash is an environmentally friendly pozzolanic material, it exhibits low early reactivity and requires activation or combination with more reactive components to be effective. Silica fume, particularly in ultra-fine form, significantly accelerates hydration and enhances C-S-H gel formation, improving the early microstructure of concrete. Slag contributes synergistically by forming C-A-S-H gel, and the best early-strength results are obtained when it is combined with Fly ash and silica. The optimal blend of these three materials can achieve compressive strength above 20 MPa in 1 day and over 40 MPa in 7 days without thermal curing. The study concludes that structured use of mineral admixtures can accelerate concrete hardening, improve construction efficiency, and support sustainable building practices. Further research is recommended at industrial scale, including exploration of locally sourced alternatives and development of data-driven predictive models